Implementation of Honesty Character in Islamic Religious Education Students Koellhoffer's Perspective - Durotul Qoyimah; Maemonah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
This study examines the implementation of honesty character in students of the Master of Islamic Religious Education (PAI) Program of UIN Sunan Kalijaga Yogyakarta from the perspective of Koellhoffer, with analytical implications, using the Lickona character framework (moral knowing, moral feeling, moral action). This study uses a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observations, and documentation, and then analyzed thematically. The results of the study show that students have a good cognitive understanding of academic honesty (originality of the work, copyright awareness, research integrity), have strong moral motivations, are often rooted in religious awareness and self-esteem, and display real behavior, such as meeting deadlines, rejecting plagiarism, and applying paraphrasing and citation techniques. However, the study also found a gap between knowledge and practice, triggered by deadline pressure, digital ease (copy-paste/AI), and the social dilemma of reprimanding friends. These findings reinforce the relevance of Koellhoffer in explaining the value of honesty and affirm Lickona's role in understanding the process of internalization to action.